Spectral characterization of optical aberrations in fluidic lenses - Puentes, Graciana; Minotti, Fernando (Frontiers in Physics, 2024)
We report an extensive numerical study and supporting experimental results on the spectral characterization of optical aberrations in macroscopic fluidic lenses with tunable focal distance and aperture shape. By using a Shack–Hartmann wavefront sensor, we experimentally reconstruct the near-field wavefront transmitted by the fluidic lenses, and we characterize the chromatic aberrations in terms of Zernike polynomials in the visible range. Moreover, we further classify the spectral response of the lenses using clustering techniques, in addition to correlation and convolution measurements. Experimental results are in agreement with numerical results based on our theoretical model of the nonlinear deformation of thin elastic membranes.